A numerical model approach of wave dynamic - Irham Muhammad; Ilhamsyah Yopi; Miswar Edy (BIO Web of Conferences, 2024)
The numerical model of wave field distribution using time dependent of wave combination from refraction-diffraction equation on a gentle slope was carried out in Modeling Laboratory of Marine and Fisheries Faculty of Syiah Kuala University. The research of numerical modeling was conducted to understand how the impact of the presence of coastal structures on the coast toward the wave dynamic approach. In the theory, the greater of wave angle, the greater of wave height distribution will be behind the breakwater, thus allowing large sediment transport to make changes to the coast. Therefore, this research is important because the knowledge of the relationship between waves and coastal structure is still limited while the dynamics of the coast have a distinctive significance in the regions. The study aims to determine the wave phenomena that interact with the structure of the coastal building so that the results of this study can be used and utilized as substantial study for future coastal planning. The method used in this study is the application of wave equations that may be solved by numerical model. The model results show that the greater the angle of incidence of waves on the southwest coast, the greater the wave height produced when it hits coastal structures. However, this characteristic does not occur in the west coast region. This is caused by the topographic nature of coastal areas and different coastal characteristics.